Segmentation Errors in the Measurement of Volumetric Parameters by Swept-Source Anterior Segment Optical Coherence Tomography - Chen, Hailiu; Meng, Jie; Lu, Peng; Ye, Dan; Li, Yunxuan; Cheng, Lu; Li, Yangyunhui; Liang, Xiaoling; Huang, Wenyong; Huang, Jingjing (Frontiers in Medicine, 2021)
Purpose: To investigate the error rate of segmentation in the automatic measurement of anterior chamber volume (ACV) and iris volume (IV) by swept-source anterior segment optical coherence tomography (SS-ASOCT) in narrow-angle and wide-angle eyes. Methods: Fifty eyes from 25 narrow-angle subjects and fifty eyes from 25 wide-angle subjects were enrolled. SS-ASOCT examinations were performed and each SS-ASOCT scan was reviewed, and segmentation errors in the automatic measurement of ACV and IV were classified and manually corrected. Error rates were compared between the narrow-angle and the wide-angle group, and ACV and IV before and after manual correction were compared. Results: A total of 12800 SS-ASOCT scans were reviewed. Segmentation error rates of angle recess, iris root, posterior surface of iris, pupil margin and anterior surface of lens were 84.06%, 93.30%, 13.15%, 59.21% and 25.27%, respectively. Segmentation errors of angle recess, iris root, posterior surface of iris and pupil margin occurred more frequently in narrow-angle eyes, while more segmentation errors of anterior surface of lens were found in wide-angle eyes (all P < 0.001). ACV decreased and IV increased significantly after manual correction of segmentation errors in both groups (all P < 0.01). Conclusion: Segmentation errors were prevalent in the volumetric measurement by SS-ASOCT, particularly in narrow-angle eyes, leading to mismeasurement of ACV and IV.